2003
DOI: 10.1073/pnas.1230951100
|View full text |Cite
|
Sign up to set email alerts
|

Lateral gene transfer and the evolution of plastid-targeted proteins in the secondary plastid-containing alga Bigelowiella natans

Abstract: Chlorarachniophytes are amoeboflagellate algae that acquired photosynthesis secondarily by engulfing a green alga and retaining its plastid (chloroplast). An important consequence of secondary endosymbiosis in chlorarachniophytes is that most of the nuclear genes encoding plastid-targeted proteins have moved from the nucleus of the endosymbiont to the host nucleus. We have sequenced and analyzed 83 cDNAs encoding 78 plastidtargeted proteins from the model chlorarachniophyte Bigelowiella natans (formerly Chlora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
188
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(206 citation statements)
references
References 36 publications
14
188
0
4
Order By: Relevance
“…As expected, a large proportion (207; 59%) of these were green algal in nature, although 45 (22%) were classified as being derived from red algae. This pattern resembles that seen in an early EST-based analysis of B. natans proteins and was attributed to the mixotrophic lifestyle of chlorarachniophyte algae 35 . For G. theta, 508 of 7,451 genes (6.8%) were deemed to be algal in origin (Fig.…”
Section: Endosymbiotic Gene Transfer and Replacementsupporting
confidence: 75%
“…As expected, a large proportion (207; 59%) of these were green algal in nature, although 45 (22%) were classified as being derived from red algae. This pattern resembles that seen in an early EST-based analysis of B. natans proteins and was attributed to the mixotrophic lifestyle of chlorarachniophyte algae 35 . For G. theta, 508 of 7,451 genes (6.8%) were deemed to be algal in origin (Fig.…”
Section: Endosymbiotic Gene Transfer and Replacementsupporting
confidence: 75%
“…1) and a similar red algal origin for this plastidial gene in Bigelowiella seems likely. Comparable cases of HGT have already been reported for these two phagotrophic complex "green algae" (Archibald et al 2003;Petersen et al 2006), and such lineage-specific acquisitions represent the fortuity of gene recruitment (Martin and Herrmann 1998). In this study, we identified two EGTs concerning SBP and plastidtargeted FBP that have important evolutionary implications.…”
Section: Diagnostic Gene Transfers Of Sbp and Fbp Document The Commonsupporting
confidence: 54%
“…Cryptophyte and chlorarachniophyte plastids still harbor highly reduced nucleomorphs, which are respectively the remnants of the nucleus of the red and green algal endosymbionts (Douglas et al 2001;McFadden 1997, 2002). With respect to their complex plastids, euglenophytes and chlorarachniophytes constitute the green lineage, whereas haptophytes, heterokonts, cryptophytes, and peridinincontaining dinoflagellates are representatives of the red lineage (Archibald et al 2003;Delwiche 1999;Li et al 2006). The affiliation of the reduced plastids of apicomplexa, including the malaria parasite Plasmodium falciparum, is unclear since both green and red algal ancestries for the apicoplast are controversially discussed (Cai et al 2003;Funes et al 2002Funes et al , 2003Waller et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…After a symbiogenetic fusion, there is extensive intracellular transfer of DNA from the organelle compartments to the nuclear genome [110,111]. Thus, most of the proteins needed for plastid and mitochondrial function are synthesized from nuclear transcripts in the cytoplasm and have to be reimported into the organelle where they act [112].…”
Section: Symbiogenesismentioning
confidence: 99%